Use of face mask in COVID-19 pandemic-a review - Swain, Santosh Kumar; Jena, Pragnya Paramita (International Journal of Research in Medical Sciences, 2021)
The current novel corona virus disease 2019 (COVID-19) is a highly infectious disease of the respiratory tract and rapidly spreading all over the world in short span of time. In current COVID-19 pandemic, use of the face mask is becoming usual and ubiquitous for both health care workers and public individuals. Wearing face mask is one of the non-pharmaceutical interventions which need minimum cost and provide dramatic response for preventing the COVID-19 infection. Limited availability of the vaccine and inadequate supply of therapeutic options, face mask use is an important part for public health measures for restricting the COVID-19 spread. Regardless of the debate among medical community regarding global face mask production shortage, a greater number of countries in the world are moving ahead with recommendations or mandates for using face mask in public. As currently global shortage of N95/FFP2 respirators and surgical masks for use by health care workers in the hospitals, simple cloth masks will act as a pragmatic solution for the use of the public. General public often use the surgical mask or even filtering facepiece (FFP) masks irrespective of their need, resulting unnecessary shortage for needy individuals those are exposed to the patients or those are health care workers. So, this review article will clarify the indication of the different types of masks and their rational use in the current COVID-19 pandemic.